INHIBITION OF CHOLESTEROL AND TRIGLYCERIDES SYNTHESIS BY COSTUS SPECIOSUS PLANT EXTRACT - Bindu; Bhat, Rama; Girish; Prasad, Krishna (International Journal of Research -GRANTHAALAYAH, 2016)
Adipocyte dysfunction plays an important role in the obesity development. People with a body weight ~ 45% heavier than the average body weight are at risk of death two times greater than the average body weight. The use of anti-obesity drugs has many side effects, so it is necessary to find the anti-obesity drug with low toxicity. Many microbial secondary metabolites and chemically synthesized antiobesity drugs are available in the market with progressive side effects upon long term use of these medicines and drugs. Plant source antiobesity drugs are potentially sustainable safe source of treatment. This ex vivo study was conducted to determine the activity of Costusspeciosus (C.speciosus) plant extract in inhibiting triglycerides and cholesterol synthesis in HepG2 cells. Anti-obesity activity includes reduced formation of lipid droplet in HepG2 cells. The triglyceride levels and Lipolytic activity by measuring cholesterol levels was performed based on commercially available kits. This study suggested that the extract of C.speciosus inhibited triglycerides and cholesterol synthesis in HepG2 cell lines with inhibition of 89.25% and 52.01% respectively at the highest concentrations tested. This study confirms that the C.speciosus extract contain anti-adipogenesis activity and has potential to inhibit the synthesis of triglycerides and cholesterol in HepG2 cell.